Plumbing - Fred Hall (Longman, 1994)
This book covers the design and installation of water supply, fire control, sanitaryappliances and drainage systems; includes up-to-date reference to relevant Bylaws, Regulations and Code of Practice where applicable; provides a comprehensive text supported by illustrations, tables and calculations; reinforces understanding by end-of-chapter test questions